Agonist-induced sensitisation of the irritant receptor ion channel TRPA1 - Meents, Jannis E.; Fischer, Michael; Mcnaughton, Peter A. (The Journal of Physiology, 2016)
KEY POINTS: The transient receptor potential ankyrin 1 (TRPA1) ion channel is expressed in nociceptive neurons and its activation causes ongoing pain and inflammation; TRPA1 is thought to play an important role in inflammation in the airways. TRPA1 is sensitised by repeated stimulation with chemical agonists in a calcium-free environment and this sensitisation is very long lasting following agonist removal. We show that agonist-induced sensitisation is independent of the agonist's binding site and is also independent of ion channel trafficking or of other typical signalling pathways. We find that sensitisation is intrinsic to the TRPA1 protein and is accompanied by a slowly developing shift in the voltage dependence of TRPA1 towards more negative membrane potentials. Agonist-induced sensitisation may provide an explanation for sensitisation following long-term exposure to harmful irritants and pollutants, particularly in the airways. ABSTRACT: The TRPA1 ion channel is expressed in nociceptive (pain-sensitive) neurons and responds to a wide variety of chemical irritants, such as acrolein in smoke or isothiocyanates in mustard. Here we show that in the absence of extracellular calcium the current passing through TRPA1 gradually increases (sensitises) during prolonged application of agonists. Activation by an agonist is essential, because activation of TRPA1 by membrane depolarisation did not cause sensitisation. Sensitisation is independent of the site of action of the agonist, because covalent and non-covalent agonists were equally effective, and is long lasting following agonist removal. Mutating N-terminal cysteines, the target of covalent agonists, did not affect sensitisation by the non-covalent agonist carvacrol, which activates by binding to a different site. Sensitisation is unaffected by agents blocking ion channel trafficking or by block of signalling pathways involving ATP, protein kinase A or the formation of lipid rafts, and does not require ion flux through the channel. Examination of the voltage dependence of TRPA1 activation shows that sensitisation is accompanied by a slowly developing shift in the voltage dependence of TRPA1 towards more negative membrane potentials, and is therefore intrinsic to the TRPA1 channel. Sensitisation may play a role in exacerbating the pain caused by prolonged activation of TRPA1.
EVALuna2:32799